2016
DOI: 10.1089/lgbt.2015.0101
|View full text |Cite
|
Sign up to set email alerts
|

A Dyadic Exercise Intervention to Reduce Psychological Distress Among Lesbian, Gay, and Heterosexual Cancer Survivors

Abstract: Purpose: Studies have found disparities in psychological distress between lesbian and gay cancer survivors and their heterosexual counterparts. Exercise and partner support are shown to reduce distress. However, exercise interventions haven't been delivered to lesbian and gay survivors with support by caregivers included. Methods: In this pilot randomized controlled trial (RCT), ten lesbian and gay and twelve heterosexual survivors and their caregivers were randomized as dyads to: Arm 1, a survivor-only, 6-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…We identified 14 studies that characterized the mental health impact and degree of adjustment to cancer . In 1 large survey study of individuals with a history of cancer that compared SGM with propensity score‐adjusted heterosexual peers, SGM survivors reported higher rates of depression and relationship difficulty .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 14 studies that characterized the mental health impact and degree of adjustment to cancer . In 1 large survey study of individuals with a history of cancer that compared SGM with propensity score‐adjusted heterosexual peers, SGM survivors reported higher rates of depression and relationship difficulty .…”
Section: Resultsmentioning
confidence: 99%
“…SM status and gender appeared to interact with symptom reporting, such that worse symptoms were reported by SGM versus heterosexual men, but not by SGM versus heterosexual women . At diagnosis, higher levels of psychosocial stress and depressive symptoms among SGM survivors were reported in a few studies, including lesbian women with breast cancer, SGM survivors enrolled in an at‐home exercise program, and survivors participating in an online survey . However, 3 studies of women with breast cancer found that SGM survivors had comparable or even better adjustment than heterosexual survivors .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions ranged from three weeks to 24 months. Only three trials had intervention outcome data that addressed the aims of this review: two studies examining the effects of interventions with versus without a partner, and a study examining a team versus group context …”
Section: Resultsmentioning
confidence: 99%
“…Perception of and satisfaction with social support in turn could be related to discrimination, degree of outness and development of sexual minority identity through stronger bonds to the LGBT community, and could mediate the impact of these factors on psychological distress (Legate, Ryan, & Weinstein, 2012). Studies that examine psychological distress in sexual minority women specifically, and that incorporate both minority stress and psychological resources, would enable more accurate screening and better tailored interventions for this underserved and at-risk group (Boehmer et al, 2013; Kamen et al, 2016). …”
Section: Introductionmentioning
confidence: 99%